Pelatihan Kewirausahaan Melalui Pengolahan Ikan Tuna Menjadi Frozen Food - Syakhuro, Moh. Hamdan; Helmi, M. Fadhlan Akbaryan; Wijaya, Dito Prakosa; Dermawan, Moh. Pebbu; Ramadhan, Dian; Saputri, Tamidhiani Dwi; Ismiati, Ismiati; Prastiwi, Yesita Ine; Fitriyani, Ardelia Nur Eka; Shakra, Riezca; Wahyuningsih, Sri Handari (Universitas Muhammadiyah Yogyakarta, 2025)
This activity was carried out in Padukuhan Bunder Kulon, Banaran Village, Galur District, Kulon Progo Regency, Yogyakarta. This activity is a compulsory campus program which is carried out for a period of one month which aims to apply the knowledge that has been learned in college to community life, starting from January 24, 2025 to February 24, 2025. The activity program in Padukuhan Bunder Kulon, Kulon Progo focuses on community empowerment related to entrepreneurship through processing tuna fish into frozen food. The main problem faced by the community is the lack of understanding of how to process tuna fish. The purpose of this activity is to improve community skills in processing tuna fish, encourage entrepreneurship, and optimize the potential of fishery resources to be more valuable and competitive. The methods used in this program include socialization and direct training to community groups. In its implementation, group 168 used experts to explain and practice directly about tuna fish processing. By bringing in experts, it is hoped that the community can implement this work program to revive the local economy. This program includes logo making, tuna fish meatball making, product packaging socialization. The results of this activity showed a significant increase in the community's understanding of how to process seafood, especially tuna into meatballs. In addition, group 168 also hopes that the work program will be sustainable, so that it will have a significant impact on the economy of the residents of Bunder Kulon Padukuhan